Aflatoxin occurrence, food regulations, dietary exposure, and risk assessment: a mini review from the malaysian perspective - Chang, Wei Lin; Abu Saad, Hazizi; Jamaluddin, Rosita; Sabran, Mohd Redzwan (Universiti Putra Malaysia, 2023)
Aflatoxins are ubiquitous and occur in food. Exposure to aflatoxins seriously impact the health of human and animal. It is concerning especially when aflatoxins are odourless, colourless, and tasteless that hardly be detected through naked eyes. Ingestion of aflatoxin-contaminated food contributes the major route of exposure. The present review is an update on the aflatoxin occurrence in food, aflatoxin regulations in food, and recent risk assessment of aflatoxin exposure in Malaysia. Peanuts and chili were more prone to aflatoxin contamination in Malaysia. The extreme weather experienced in Malaysia and global climatic change may worsen the aflatoxin contamination in food. The regulatory standards for aflatoxins imposed by Malaysia are less stringent than developed countries. The dietary exposure of aflatoxins among Malaysian was relatively high as compared with other Asia countries, ranging from 0.002 to 34.00 ng/kg body weight/day. Nonetheless, Malaysian population had low risk of aflatoxin-related liver cancer, with an estimated liver cancer risk of <1 cancer case/100,000 population/year.